FACTORS RELATED TO AGE OF MENARCHE IN ADOLESCENT WOMEN - Jumiyati Jumiyati (Universitas Islam Negeri Alauddin Makassar, 2022)
Backgrounds: Menarche is the first bleeding from the uterus that occurs in a woman. Menarche is caused by several factors including nutritional status, ethnicity, genetics, social, economic, etc. Objective: This study aims to determine the relationship between diet, food intake, nutritional status and exposure to social media with the age of menarche in adolescent girls at SMPN 1 Kolaka in 2021. Method: The type of research used is a cross sectional research design and the sample taken is 136 respondents and the sample is taken by stratified proportional random sampling. Statistical analysis used in this study is the chi square test. The research results are said to be related if the results of the statistical test p value <0.05. Result: The results showed that on average the respondents had an early menarche age of 55.1%. Most of the respondents have a good diet and intake of food as much as 86.8%. As many as 80.9% of respondents have normal nutritional status and as many as 72.1% of respondents have been exposed to social media. Conclusion: Based on the results of the study, it can be concluded that the variables between diet, food intake, nutritional status and exposure to social media with age at menarche of respondents have a significant relationship.